ANDROGEN RECEPTOR VALUES FOR PREDICTION OF SURVIVAL OF PATIENTS WITH THREE TIMES NEGATIVE BREAST CANCER - Atakhanova N.E; Almuradova D.M; Gaziev L.T; Sadullaeva N.I; Erkinova Ch.O (Scholar Express Journals, 2023)
Breast cancer retains its leading position in terms of the incidence of malignant neoplasms in women. Triple negative breast cancer (TNBC) accounts for 12–20% of the entire group of breast cancers (BC). TNBC is characterized by the absence of estrogen receptors (ER), progesterone receptors (PR) and HER-2/ neu expression. This study shows that the presence and detection of androgen receptors (AR) by IHC-expression of TN breast cancer cells opens up prospects for the development of targeted therapy for this type, taking into account the presence or absence of androgen receptors. To rationalize the therapy of TN in breast cancer, it is certainly necessary to summarize a large number of materials with a thorough analysis of all clinical and morphological parameters, taking into account survival rates and the options for chemotherapy regimens used. Thus, breast cancer TN is currently an unresolved scientific and practical problem in the field of oncology, requiring additional research both in terms of finding optimal approaches to the use of already available diagnostic and treatment options, and in searching for new treatment options, as well as fundamental research. in the field of studying the biological characteristics of the disease. The definition of AR is an important factor that plays a role in the prognosis of breast cancer in all molecular subtypes, especially in TN breast cancer, which can become a targeted target for planning targeted therapy. In the course of the study, informative and significant clinical, morphological and parameters were studied and determined on the basis of the prognosis model, allowing with a sufficient degree of probability to predict the outcome of the disease in patients with TN, including when determining a positive AR status, which determines a more favorable prognosis. The presence and detection of androgen receptors (AR) by TN breast cancer cells during IHC-expression opens up prospects for the development of targeted therapy for this type, taking into account the presence or absence of androgen receptors
Keywords: triple negative breast cancer; androgen receptor; prognosis